Granulocytes Acquire Antiapoptosis Activity and Promote Tumor Growth during Tumor Progress - Li, Han; Shen, Wenyan; Xu, Yanjie; Wang, Zien; Wang, Linghao; Ding, Zequn; Xie, Zhiyuan; Zhang, Yan (Global Medical Genetics, 2021)
Granulocytes play important roles in cancer, and their apoptotic status is often changed by the influence of tumor environment. However, the changes and the function on granulocyte apoptosis in cancer are unclear. In this study, we used tumor-bearing mouse model and tumor patients to analyzed the apoptosis of granulocytes in different tissues by flow analysis and TUNEL fluorescence staining, and found that the percentage of apoptosis cells in granulocytes was significantly decreased in late-stage tumor-bearing mouse and patients. The in vitro co-culture experiment showed that these antiapoptotic granulocytes could significantly inhibit T cell proliferation, and RNA-seq proved that there was obvious difference on the transcriptome between these cells and control cells, particularly immune-related genes. What is important, adoptive transfer of these antiapoptotic granulocytes promoted tumor progress in mouse model. Conclusively, we found that granulocytes in late-stage tumor could delay the process of apoptosis, inhibit T cell proliferation, and acquire pro-tumor activity, which provides a new therapeutic target for tumor immunity.
Keywords: granulocyte; apoptosis; cancer